Pengaruh Jenis Persalinan Terhadap Kejadian Post Partum Blues di RSUD dr. MM. Dunda Limboto Kabupaten Gorontalo Provinsi Gorontalo - Windi Ismail; Rizky Nikmathul Husna; Dwi Nur Octaviani; Siskawati Umar (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2019)
Post-partum blues is sad feeling or glum in mothers after childbirth. It usually appears temporarily, around two days to two weeks since the birth of the baby. The types of childbirth can be trigger for the emersion of post-partum blues symptoms. This research was conducted at Dr. MM Dunda hospital, Limboto, Gorontalo Regency. The aim of this research was to determine the type of childbirth on post-partum blues at Dr. MM Dunda Hospital, Limboto. This type of research is quantitative research with descriptive analytic methods and cross-sectional approaches. There were 38 samples in this research who were taken by using Purposive sampling. The result of data analysis showed that p-value = 0.005 <α 0.05. it can be inferres that there is a significant relationship between the types of childbirth and post-partum blues.